قرآن کریم کی سورتوں اورآیات میں ربط ومناسبت کی اقسام وانواع کا تحقیقی جائزہ: The classification of relativity in surahs And verses of the Holy Quran - Dr. Muhammad Khurram; Akhlaq Ahmed; Muhammad Zakir Khan (Al Manhal Research Journal, 2024)
As per findings of the scholars, there are various inter-connections among Quranic verses. The most important among these are internal and external. The aim is to show the links of one surah with the other or within one surah. The internal link shows the connection within a single surah and it further entails the link at the start and end of surah or with the title of surah. While on the other hand, the external link means the link of one surah with the previous one, their themes and the endings of both surahs.